The comparative analysis of statistics, based on the likelihood ratio criterion, in the automated annotation problem - Leontovich, Andrey M (BioMed Central, 2008)
BACKGROUND: This paper discusses the problem of automated annotation. It is a continuation of the previous work on the A(4)-algorithm (Adaptive algorithm of automated annotation) developed by Leontovich and others. RESULTS: A number of new statistics for the automated annotation of biological sequences is introduced. All these statistics are based on the likelihood ratio criterion. CONCLUSION: Some of the statistics yield a prediction quality that is significantly higher (up to 1.5 times higher) in comparison with the results obtained with the A(4)-procedure.